Ang Lihim sa loob ng mga pader - Evasco, Eugene Y. (Philippine humanities review = Rebyu ng Arte at Literatura ng Pilipinas.)
"...avoids the stereotypical depiction of the Spanish friar as the evil enemy but instead presents a priest, who out of his genuine interest in Philippine plants, studies them and even helps heal the dog of a Filipino boy who befriends him. This is perhaps one of the first children's story that has for a major character, a compassionate Spanish friar who, without hesitation, goes out of the walls of Intramuros in order to cure the indio." -- Introduction